SAMPAH SEBAGAI MASALAH SOSIAL DI KOTA SINTANG: PERSPEKTIF STRUKTURAL DAN KULTURAL - Markus Markus (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2025)
The waste problem in Sintang City reflects a complex social issue, involving interconnected structural and cultural factors. This study aims to analyze waste management issues in Sintang City through structural and cultural approaches and identify potential solutions that can be implemented. Using qualitative methods such as interviews, focus group discussions, and observations, the research finds that from a structural perspective, the main challenges include a lack of waste management infrastructure, suboptimal implementation of policies, and limited tripartite coordination between the government, community, and private sectors. Meanwhile, from a cultural perspective, low public awareness of the importance of waste management, a culture of consuming waste-generating products excessively, and the habit of littering pose significant barriers to creating a clean and healthy environment. Community-based approaches, such as environmental education, waste bank programs, and community group empowerment, can enhance public awareness and participation in waste management. The findings also indicate that the waste problem in Sintang City is not merely a technical issue but a social one that requires a holistic approach. Therefore, collaboration among adaptive policies, adequate infrastructure, and behavioral change within the community is key to establishing a sustainable waste management system.